Structural Morphology: An Effective Solution for Generating Efficient Structural Forms - Srisuwan, Touchaphong (International Journal of Building, Urban, Interior and Landscape Technology, 2021)
Many natural forms have been imitated by architects and designers and applied to the design process in order to achieve the most efficient solution for structural arrangement and architectural form. The integration of knowledge in biology and structure in nature is an approach to structural morphology that offers the possibility of developing innovative forms and efficient structural prototypes. This review introduces the fundamental concept of structural morphology based on form-finding and structural optimization through the works of the biologist D’Arcy Thompson, the theory of Michell and the experimental studies of pioneers like Antoni Gaudi, Frei Otto and Heinz Isler. Some examples of buildings using structural morphology as effective design solutions are illustrated to substantiate the potential applications in architecture.